Home Care Delivery and Remote Patient Monitoring of Kidney Transplant Recipients During COVID-19 Pandemic. (December 2021) - Chang, Jae-Hyung; Sritharan, Sharlinee; Schmitt, Kevin; Patel, Shefali; Crew, R. John; Tsapepas, Demetra S.
Telehealth plays a critical role in the response of healthcare organizations during the COVID-19 pandemic. While telemedicine offers a real-time patient-provider encounter, the inability to obtain vital signs during virtual visits is a potential limitation. Remote patient monitoring (RPM) uses portable devices in the patient's home to collect and electronically transmit physiological data to clinicians. Two kidney transplant recipients were enrolled in RPM in their immediate post-transplant period. Real-time monitoring of their physiological data at home through the RPM in combination with the ability to titrate medications resulted in normalization of the blood pressure and blood glucose measurements by six weeks. Our initial experience demonstrates that RPM is feasible and effective in the post-transplant period and can expand care opportunities on the remote care model. This is more relevant than ever as remote monitoring can facilitate the care of COVID-19-positive transplant patients who require close monitoring while isolated at home.